The Literary Competence for the Spanish Foreign Language Classroom - Luján-Ramón, Salvadora (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
Theoretical and practical argumentation on the development of literary competence in the Spanish Language classroom, unifying guidelines for implementation as an essential vertex for the acquisition of communicative competence.